Theoretical Foundations of Cultural Materialism and Understanding of Literary Text - Dr. Mujahid Abbas; Dr. Kamran Abbas Kazmi (دریافت)
Cultural Materialism theory is proposed by an American Anthropologist Marvin Harris. This theory has a scientific strategy to find the facts about human cultures. This theory suggests that in every sociocultural system, three major parts, infrastructure, structure, and superstructure, interact with each other. Infrastructure refers to material resources of the culture that man established to get energy and food from his physical environment. Structure refers to the laws and procedures of social institutions which regulate the distribution of food and power among the members of the society. Superstructure refers to the soft images of society like art, music, language, literature, and behaviors of individuals in a social setup. This theory provides a comprehensive analysis pattern of any literary text by finding the infrastructure in the base of structure and superstructure. In this article, it is tried to formulate theoretical bases and practical dimensions of cultural materialism۔